A novel common control channel security framework for cognitive radio networks. (3rd April 2012) - Safdar, G.A.; O'Neill, M.
Cognitive radio technology makes use of the underutilised spectrum opportunistically without causing interference to the primary users. Cooperatively communicating cognitive radio devices use the common control channel of the cognitive radio medium access control to perform free channel announcements, channel selection and channel reservation before any actual data transmission. Common control channel security is vital in order to ensure security in the subsequent communication among the cognitive radio nodes. Additional to well-known security problems in wireless networks, cognitive radio networks introduce new classes of security threats and challenges, such as misbehaviours in spectrum sensing, licensed user emulation and attacks in the common control channel transactions. This paper presents a novel common control channel security framework (protocol) for cooperatively communicating cognitive radio networks. To the best of the authors' knowledge, this is the first paper to address the security requirements of the common control channel. An implementation of the proposed security protocol is discussed illustrating how two cognitive radio nodes can authenticate each other prior to any confidential common control channel negotiations. The protocol is formally validated by GNY logic and a security analysis of the protocol illustrates that it meets the principal security requirements of authentication, confidentiality, integrity and non-repudiation